Comparative Characteristics of Morphometric Parameters of the Spleen After Hormonal Therapy of Intestinal Scar Processes in Experimental Conditions (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Analysis of the literature shows that with a short-term course of hormonal drugs administered to rats, as a result of macro- and microscopic studies, a decrease in immunogenesis, degenerative changes in splenic follicles, and some increase in the relative mass of the spleen were revealed. At the same time, it remains relevant for researchers to study the morphometric and immunohistochemical indices of the spleen, which is sensitive to homeostasis disorders, after hormonal therapy of cicatricial processes in the experimental intestine.